Influence of Glutamic Acid Enantiomers on C‐mineralization. Issue 2 (6th November 2014) - Formánek, Pavel; Vranová, Valerie; Lojková, Lea
Abstract Seasonal dynamics in the mineralization of glutamic acid enantiomers in soils from selected ecosystems was determined and subjected to a range of treatments: ambient x elevated CO2 level and meadow x dense x thinned forest environment. Mineralization of glutamic acid was determined by incubation of the soil with 2 mg L‐ or D‐glutamic acid g‐1 of dry soil to induce the maximum respiration rate. Mineralization of glutamic acid enantiomers in soils fluctuates over the course of a vegetation season, following a similar trend across a range of ecosystems. Mineralization is affected by environmental changes and management practices, including elevated CO2 level and thinning intensity. L‐glutamic acid metabolism is more dependent on soil type as compared to metabolism of its D‐enantiomer. The results support the hypothesis that the slower rate of D‐ compared to L‐ amino acid mineralization is due to different roles in anabolism and catabolism of the soil microbial community. Chirality 27:104–108, 2015. © 2014 Wiley Periodicals, Inc.